Selected strains of the Ganoderma lucidum complex from Finnish forests have excellent broadly acting antiviral properties - Reshamwala, Dhanik; Shroff, Sailee; Liimatainen, Jaana; Tienaho, Jenni; Kuukkanen, Ilari; Laajala, Mira; Civra, Andrea; Francese, Rachele; Veteli, Pyry; Cortina-Escribano, Marta; Sarjala, Tytti; Karonen, Maarit; et al. (Springer Nature, 2025)
Broadly acting antivirals are needed to complement vaccines in present and future pandemics and outbreaks as safe and sustainable tools for combating virus infections. Thus, the current study aims to investigate the broad-spectrum antiviral activity of ferments of selected strains belonging to the Ganoderma lucidum complex isolated from Finland and investigate their mechanism of action. Cytopathic effect inhibition assay and endpoint assay were used to determine the antiviral activity. The antibacterial activity ws examined using recombinant biosensor strains. Mechanism of action studies included time of addition assay, transmission electron microscopy, confocal microscopy, sucrose gradient separation assay, and thermal assay. The metabolite composition of the ferments was studied using UHPLC-HR-MS/MS. Ferments showed antiviral efficacy against non-enveloped enteroviruses, already at room temperature and within one minute. Broad antimicrobial activity was demonstrated with non-enveloped rotaviruses, enveloped coronaviruses, zika viruses, and gram-positive and gram-negative bacteria. Ferments also directly affected the viruses and caused clustering of the virus particles. Additionally, treatment of enteroviruses with ferments caused strong stabilization of the virus capsid, thus preventing their genome release. UHPLC-HR-MS/MS analysis of the ferments verified the presence of several terpenoid compounds. The results show great promise for the future use of ferments from the Ganoderma lucidum complex in combating microbial infections for various applications.
Keywords: antimicrobial; broad-spectrum; stabilization; enteroviruses; Ganoderma sp. ferment; coronaviruses